Pseudopotential model and correlation functions of semiclassical partially ionized plasmas - Davletov, A. E. (Recent Contributions to Physics, 2008)
Pseudopotential model of particle interaction in semiclassical partially ionized plasmas, taking into account both quantum-mechanical effects and presence of the neutral component (atoms), is proposed. Radial distribution functions and static structure factors are investigated for he case of hydrogen plasmas. 91 Possibility of the short-range order formation is shown for the plasma-neutral gas system even for small values of the coupling parameter related to the nonideality in particle interaction.
Keywords: Pseudopotential model